Penerapan Manajemen Resiko: Studi Kasus pada UMKM Anukula Cafe & Resto (Brand Es The 2000an dan Kebab Burger Mirasa) - Riki Gana Suyatna; Annisa Nurfadilla (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Risk management is very important for MSMEs because risk management is useful for gathering information about possible risks that will occur, as well as for developing strategies that need to be implemented at Anukula Resto MSMEs, where Anukula Resto itself is an MSME that is engaged in selling food and drinks such as ice the 2000s and kebabs. mirasa burger. This research aims to determine the implementation of risk management and describe or illustrate the activities of the MSMEs Anukula Resto Serang. This research uses a qualitative descriptive approach using risk analysis in management. The results of the analysis show that the implementation of risk management at Anukula Resto MSMEs has been implemented well for financial risks, marketing risks, while for HRM risks it is still not good. It is proven that there are still errors in the calculations carried out by HR at the Anukula Resto UMKM. Therefore, it is important for Anukula Resto MSMEs to improve and implement risk management well in order to minimize risks that occur in the future.